2013
DOI: 10.1152/ajpregu.00434.2012
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of capillaries in skeletal muscle of nNOS-knockout mice

Abstract: Because neuronal nitric oxide synthase (nNOS) has a well-known impact on arteriolar blood flow in skeletal muscle, we compared the ultrastructure and the hemodynamics of/in the ensuing capillaries in the extensor digitorum longus (EDL) muscle of male nNOS-knockout (KO) mice and wild-type (WT) littermates. The capillary-to-fiber (C/F) ratio (-9.1%) was lower (P ≤ 0.05) in the nNOS-KO mice than in the WT mice, whereas the mean cross-sectional fiber area (-7.8%) and the capillary density (-3.1%) varied only nonsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…However, we found that capillary density was unaffected in GSNOR -/-TA muscles and that HIF1a transcript was unaffected, whereas HIF1a protein was undetectable (data not shown). These findings agree with a recent study suggesting that the primary source of skeletal muscle NO, nNOSl, is dispensable for capillary density (6). These data suggest that angiogenesis is differentially regulated by GSNOR during skeletal and cardiac muscle development, and they argue against increased capillary density as an important factor in the augmented fatigue resistance of GSNOR -/-mice.…”
Section: Discussionsupporting
confidence: 92%
“…However, we found that capillary density was unaffected in GSNOR -/-TA muscles and that HIF1a transcript was unaffected, whereas HIF1a protein was undetectable (data not shown). These findings agree with a recent study suggesting that the primary source of skeletal muscle NO, nNOSl, is dispensable for capillary density (6). These data suggest that angiogenesis is differentially regulated by GSNOR during skeletal and cardiac muscle development, and they argue against increased capillary density as an important factor in the augmented fatigue resistance of GSNOR -/-mice.…”
Section: Discussionsupporting
confidence: 92%
“…The mean capillary‐to‐fibre ratio was calculated using ImageJ, version 1.47 (National Institutes of Health, Bethesda, MD, USA) as described previously (Baum et al . ). Image collections and quantifications were performed blinded.…”
Section: Methodsmentioning
confidence: 97%
“…The mean cross‐sectional fibre area was estimated by point counting, and capillary profile density and capillary‐ to ‐fibre (C/F) ratio were calculated, as previously described (Baum et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…If a particle falls inside of the counting frame and does not cross a forbidden line it is counted, whereas it is not counted if it touches one of the forbidden lines (Weibel 1979). The mean cross-sectional fibre area was estimated by point counting, and capillary profile density and capillary-to-fibre (C/F) ratio were calculated, as previously described (Baum et al 2013).…”
Section: Light Microscopymentioning
confidence: 99%